The Effect of the Van Haaal Model on the Development of Geometrical Thinking in Seventh-Grade Mathematics Students - Mamoud, Dr. Moayyad Mohammad Mahmoud; Karim, Asst.L. Befrin Gharib Ghafoor Karim (Sulaimani Journal for Humanities, 2025)
The aim of the study is to determine how the Van Hiele model affects the development of geometric thinking among seventh-grade math students. To achieve the objective of the study, the empirical method was applied. The research requirements are prepared, which include defining the scientific topic, developing behavioral goals, preparing a daily schedule, and designing and creating a geometric thinking test. The geometric thinking test consists of five skills and ten articles. After validating the test's correctness and stability, it was determined that both were high and acceptable. The experiment was implemented on 66 students, with an experimental group of 33 and a control group of 33 at Shad Primary School for the academic year 2023-2024. Both study groups were equal in terms of students' age in months, the initial test of geometric thinking, Raven's intelligence test, previous experience, and first semester grades. The researchers taught experimental groups according to the five-level Van Hiele model and control groups in the normal way.Following the end of the experiment, both groups were given a geometric thinking test. A variety of appropriate statistical tools have been utilized, including Person's equation, arithmetic mean, standard deviation, and the T-test. The results illustrated that there was a statistical difference at the level of evidence 0.05 between the mean scores of the students of both study groups for the geometric thinking test in favor of the experimental group. The study's recommendations include using the Van Hiele model in primary school mathematic subjects and offering training courses for mathematics instructors of all grades to learn about geometric thinking and skills.
Keywords: Van Hiele model; geometric thinking